Pertactin-deficient Bordetella pertussis isolates: evidence of increased circulation in Europe, 1998 to 2015 - Barkoff A-M.; Mertsola J.; Pierard D.; Dalby T.; Hoegh S.V.; Guillot S.; Stefanelli P.; van Gent M.; Berbers G.; Vestrheim D.; Greve-Isdahl M.; Wehlin L.; et al. (EUR CENTRE DIS PREVENTION & CONTROL, 2022)
Introduction: Pertussis outbreaks have occurred in several industrialised countries using acellular pertussis vaccines (ACVs) since the 1990s. High prevalence of pertactin (PRN)-deficient Bordetella pertussis isolates has been found in these countries. Aims: To evaluate in Europe: (i) whether proportions of PRN-deficient strains increased in consecutive collections of B. pertussis clinical isolates; (ii) if the frequency of PRN-deficient strains in countries correlated with the time since ACV introduction; (iii) the presence of pertussis toxin (PT)-, filamentous haemagglutinin (FHA)- or fimbriae (Fim)-deficient isolates. Methods: B. pertussis clinical isolates were obtained from different European countries during four periods (EUpert I-IV studies): 1998 to 2001 (n =102), 2004 to 2005 (n =154), 2007 to 2009 (n =140) and 2012 to 2015 (n=265). The isolates' selection criteria remained unchanged in all periods. PRN, PT, FHA and Fim2 and Fim3 expression were assessed by ELISA. Results: In each period to1.0% (1/102), 1.9% (3/154), 6.4% (9/140) and 24.9% (66/265) of isolates were PRN-deficient. In EUpert IV, PRN-deficient isolates occurred in all countries sampled and in six countries their frequency was higher than in EUpert III (for Sweden and the United Kingdom, p < 0.0001 and p = 0.0155, respectively).Sweden and Italy which used ACvs since the mid 1990s had the highest frequencies (69%; 20/29 and 55%; 11/20, respectively) while Finland, where primary immunisations with ACV containing PRN dated from 2009 had the lowest (3.6%). Throughout the study, no PT- or FHA-deficient isolate and one Fim2/3-deficient was detected. Conclusion: Results suggest that the longer the period since the introduction of ACVs containing PRN, the higher the frequency of circulating PRN-deficient isolates.